Outcomes of perioperative vasopressor use for hemodynamic management of patients undergoing free flap surgery: A systematic review and meta‐analysis. Issue 3 (8th January 2023) - Michelle, Lauren; Bitner, Benjamin F.; Pang, Jonathan C.; Berger, Michael H.; Haidar, Yarah M.; Rajan, Govind R.; Tjoa, Tjoson
Abstract: This systematic review and meta‐analysis investigates the objective evidence regarding outcomes in head and neck free flap surgeries using vasoactive agents in the perioperative period. A search was performed in PubMed, Cochrane, Web of Science, and Scopus databases. Inclusion criteria were clinical studies in which vasopressors were used in head and neck free flap surgery during the intraoperative and perioperative period. Eighteen studies ( n = 5397) were included in the qualitative analysis and nine ( n = 4381) in the meta‐analysis. There was no difference in flap failure outcomes with perioperative vasopressor use in head and neck free flap surgery ( n = 4015, OR = 0.93, 95% CI [0.60, 1.44]). When patients received vasopressors perioperatively, there was an associated decrease in flap‐specific complications ( n = 3881, OR = 0.69, 95% CI [0.55, 0.87]). Intraoperative vasopressor use does not negatively impact free tissue transfer outcomes in head and neck surgery and may reduce overall free flap complications.